Організація роботи рекламного агентства - Оліярник, Христина; Кравець, Руслан (Видавництво Львівської політехніки, 2014)
The process of creating advertising activity is the production of advertising agency, that its main function. As a result of this process we get the product of agency – advertising that addresses the needs of the customer.
Keywords: реклама; BTL; рекламне агентство; промоутер; промо-акція; рекламні послуги